(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
In terms of waste management practices, it was normal practice in the late 1800s to send bargesloaded with municipal rubbish out to sea for open disposal. Regular waste disposal into the watersuggests that there was little awareness of or concern for the effects on the ecosystem. The FresnoSanitary Landfill was constructed in 1937 before there was a big change from open dumping. Reducingsolid waste means less garbage ends up in landfills. The most popular ways to reduce landfill waste areto reduce, reuse, and recycle. Landfill waste is a major issue since it affects both the economy and theecology, and also because it takes thousands of years for landfill material to decompose, renderingseveral acres of land that could have been used for new industrial or residential colonies essentiallyunusable.